2011
DOI: 10.1371/journal.pone.0026622
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Loss Reduces the DNA-Binding of BMAL1, CLOCK, and NPAS2 to Specific Clock Genes in the Mouse Cerebral Cortex

Abstract: We have previously demonstrated that clock genes contribute to the homeostatic aspect of sleep regulation. Indeed, mutations in some clock genes modify the markers of sleep homeostasis and an increase in homeostatic sleep drive alters clock gene expression in the forebrain. Here, we investigate a possible mechanism by which sleep deprivation (SD) could alter clock gene expression by quantifying DNA-binding of the core-clock transcription factors CLOCK, NPAS2, and BMAL1 to the cis-regulatory sequences of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 74 publications
7
70
0
Order By: Relevance
“…4C), showing a peak at ZT6 and a trough around dark-light transition (ZT18-ZT0). This phase is similar to what we recently observed for binding to several clock genes (41). Furthermore, and also similar to our previous data (41), we found that SD decreases the binding of those transcription factors to the Nlg1 E-box (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…4C), showing a peak at ZT6 and a trough around dark-light transition (ZT18-ZT0). This phase is similar to what we recently observed for binding to several clock genes (41). Furthermore, and also similar to our previous data (41), we found that SD decreases the binding of those transcription factors to the Nlg1 E-box (Fig.…”
Section: Resultssupporting
confidence: 92%
“…These last two observations parallel changes in the expression of Nlg1 with B, which provide support for a transcriptional control of Nlg1 with insert B by clock transcription factors. Thus, during enforced wakefulness, prolonged high neuronal activity could decrease CLOCK/BMAL1 binding to Nlg1 Eboxes as it does for other CLOCK/BMAL1 targets (41). This would lead to reduced expression of Nlg1 with B and NLG1 at the synapse and consequently to impaired NMDAR function (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the levels and activity of Bmal1, Npas2, and Clock are intimately tied to circadian oscillation, and conditions that disrupt oscillation can suppress Bmal1 expression or transcriptional activity. These include cellular senescence, sleep deprivation, and pulsed-light exposure (44)(45)(46). Therefore, these circadian "stressors" may predispose individuals to age-related neurodegeneration by suppressing positive-limb clock gene expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Within this critical region, two TF motifs were identified: a consensus E-box motif (recognized by bHLH TFs) (Massari and Murre 2000), immediately next to a motif recognized by basic region leucine zipper (bZIP) proteins of the AP-1 family (Heinz et al 2010). Like neural bHLH proteins, AP-1 family proteins are known to have important roles in regulating gene expression in the cerebral cortex (Raivich and Behrens 2006;Mongrain et al 2011).…”
Section: Wwwgenomeorgmentioning
confidence: 99%